Animals Erased: Discourse, Ecology, and Reconnection with the Natural World - Stibbe, Arran (Wesleyan University Press, 2012)
<![CDATA[Animals are disappearing, vanishing, and dying out--not just in the physical sense of becoming extinct, but in the sense of being erased from our consciousness. Increasingly, interactions with animals happen at a remove: mediated by nature programs, books, and cartoons; framed by the enclosures of zoos and aquariums; distanced by the museum cases that display lifeless bodies. In this thought-provoking book, Arran Stibbe takes us on a journey of discovery, revealing the many ways in which language affects our relationships with animals and the natural world. Animal-product industry manuals, school textbooks, ecological reports, media coverage of environmental issues, and animal-rights polemics all commonly portray animals as inanimate objects or passive victims. In his search for an alternative to these negative forms of discourse, Stibbe turns to the traditional culture of Japan. Within Zen philosophy, haiku poetry, and even contemporary children's animated films, animals appear as active agents, leading their own lives for their own purposes, and of value in themselves.]]>